Time Slots Allocating and Multicycle Scheduling in IWSN for Narrow Process Automation. (18th June 2014) - Xu, Honghua; Liu, Ke; Guan, Xinping
Industrial wireless sensor networks (IWSNs) have become a viable solution for diverse application. However, commercial products and real-world deployments of IWSNs are faced with harsh reliability, real time, and predictability issues. The problem is more challenging in the narrow process industry. A novel two-tier wireless network consisting of subnetworks (FNs) and a backbone (BN) in the field is proposed in this paper. Along exploring time and frequency diversity, we present an optional polling slots allocation method in the FN to maximize communication reliability and integrity. Since time slots are scarce in the communication network for narrow process, we design a slot-reuse strategy with time slots consumption of2 * N to construct a N -hop multipath BN without violating industrial standard. Furthermore, a multicycle scheduling strategy for polling and convergecast is presented to reduce the workload over the BN. Performance analysis and simulations show that our solution outperforms traditional ones in terms of communication reliability and integrity.